A triphenylamine-based aggregation-enhanced emission probe for viscosity and polarity analysis of lubricating oils. Issue 7 (19th January 2022) - Jia, Pengxiao; Wang, Fu; Zeng, Wei; Wang, Zhaofeng
Abstract : This work provides an effective molecule-based method for the viscosity and polarity analysis of lubricating oils. Abstract : Lubricating oils offers abundant information about the operating state of machines. In this work, a donor–acceptor aggregation-enhanced emission fluorescent molecule, ( Z )-4-(1-cyano-2-(4-(diphenylamino)phenyl)vinyl)benzonitrile (CPA–TPA), was synthesized to investigate its function to sense the viscosity and polarity of lubricant base oils. The results indicated that the molecule showed steadily-increased fluorescence emission with the base oil viscosity. In a mixture of poly-α-olefin/ester base oils, its optimal emission gradually red-shifted with the ester oil fraction, i.e., the polarity of the lubricant. A good correlation could be established between the emission intensity of the probe and the oil viscosity or between the optimal emission wavelength and the oil polarity. This demonstrates a dual-response fluorescent probe used for lubricating oil analysis and opens a new opportunity to develop a molecule-based method for the evaluation of lubricating oil quality.